Elementary EFL teachers’ perceptions on code-switching in primary learning contexts - Kristian Florensio Wijaya; Retno Muljani Retno Muljani; Barli Bram (Universitas Sarjanawiyata Tamansiswa, 2020)
In this 21st century teaching and learning, there is an intense debate involving language experts whether code-switching should be integrated into EFL learning contexts or not. The supporters of the L2 believed that intense training in the target language will enable EFL learners to be more proficient target language users. While the L1 experts allowed EFL teachers to apply their mother tongue while delivering the teaching-learning materials in order to deliver their teaching-learning instructions clearly for the learners. In line with this contradictory paradigm, EFL teachers need to implement the first language more judiciously in order to preserve learners’ first language and acquire their target language competencies fully. This study attempted to discover Elementary EFL teachers’ perceptions of the use of code-switching in primary learning contexts. This study utilized narrative inquiry utilizing one research instrument, open-ended interview questions to discover Elementary EFL teachers’ perceptions regarding the utilization of code-switching in primary learning contexts. The participants involving in this study were EFL teachers working in Demangan Baru 1 Elementary School, Yogyakarta. Findings from this study revealed that code-switching did not only help EFL teachers to deliver particular learning materials clearly but also promote greater EFL learning enjoyment for the students.